2022
DOI: 10.1002/acr.24716
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Behavioral Changes, and Low Seroprevalence of SARS–CoV‐2 Antibodies in Patients With Systemic Lupus Erythematosus or Rheumatoid Arthritis

Abstract: Objectives Patients with chronic rheumatic diseases (CRD), such as Systemic Lupus Erythematosus (SLE) and Rheumatoid Arthritis (RA), require special attention during the COVID‐19 pandemic, as they are considered at risk of severe infections. We assessed the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibodies in patients with SLE and RA and patient behavior, disease‐related symptoms, and mental health. Methods More than 900 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…This and the absence of SARS-CoV2 antibodies in pre-pandemic sera suggests that molecular mimicry is an unlikely explanation for SARS-CoV-2 seropositivity. 6 Like other reports, 3,7,8 our SLE cohort had a lower rate of seropositivity pre-pandemic and a slightly lower to similar rate of seropositivity intra-pandemic compared to contemporaneous controls. In contrast, over a similar observation period, others reported that 4% (4/100) SLE patients had PCR-confirmed infection, but 36% showed SARS-CoV-2 antibodies of at least one isotype, particularly IgA and IgM.…”
Section: Sars-cov-2 Seroprevalence Seroconversion and Neutralizing Antibodies In A Systemic Lupus Erythematosus Cohort And Comparison To supporting
confidence: 85%
“…This and the absence of SARS-CoV2 antibodies in pre-pandemic sera suggests that molecular mimicry is an unlikely explanation for SARS-CoV-2 seropositivity. 6 Like other reports, 3,7,8 our SLE cohort had a lower rate of seropositivity pre-pandemic and a slightly lower to similar rate of seropositivity intra-pandemic compared to contemporaneous controls. In contrast, over a similar observation period, others reported that 4% (4/100) SLE patients had PCR-confirmed infection, but 36% showed SARS-CoV-2 antibodies of at least one isotype, particularly IgA and IgM.…”
Section: Sars-cov-2 Seroprevalence Seroconversion and Neutralizing Antibodies In A Systemic Lupus Erythematosus Cohort And Comparison To supporting
confidence: 85%
“…Thus, a recent study showed seroprevalence of SARS-CoV-2 antibodies among blood donors to be several-fold higher (1.9%) than among patients with chronic rheumatic diseases (0.3%). Thus, we speculate that the risk of infection was lower among people with preexisting disease [ 36 ]. Plausible mechanisms to explain this include increased compliance regarding social distancing and self-isolating after exposure to close encounters of COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were recruited from the COPANARD (Corona Pandemic Autoimmune Rheumatic Disease) cohort [3]. Outpatients with SLE or RA were identified through hospital records at the Department of Rheumatology, Aarhus University Hospital, Denmark.…”
Section: Subjectsmentioning
confidence: 99%
“…American College of Rheumatology (ACR) has recommended vaccination of patients with rheumatic diseases and considers this group to be at higher risk of severe COVID-19 than the general population [1,2]. A further encouragement of vaccination has been that the COVID-19 pandemic has prompted isolation in patients with rheumatic diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%